KUALITAS PELAYANAN DALAM PEMBUATAN SURAT KETERANGAN TIDAK MAMPU (SKTM) PADA PROGRAM BANTUAN SOSIAL (BANSOS) - Bunga Sari, Affa; Nurcahyanto, Herbasuki; Lestari, Hesti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The aim of this research is to analyze the quality of service in making Unable Certificates (SKTM) for the Social Assistance Program in Bulakan Sub-District, Sukoharjo Subdistrict. This research uses Zeithaml's theory which consists of the dimensions of Tangible, Reliability, Responsiveness, Assurance, and Empathy, GAP Model, and Importance Performance Analysis (IPA). This type of research uses a quantitative approach with descriptive research type. The population of this study was all visitors to Bulakan Sub-District, Sukoharjo Subdistrict using a purposive sampling technique of 96 respondents. The results of the research show that the overall service in making Unable Certificates for the Social Assistance Program in Bulakan Sub-District, Sukoharjo Subdistrict has an average level of service performance and an average level of service expectations which shows that the services provided are included in the category good. Based on the five dimensions of service quality, there is one dimension that is not optimal, namely the Responsiveness dimension.